Design of a microstrip antenna patch with a rectangular slot for 5G applications operating at 28 GHz - Salah-Eddine Didi; Imane Halkhams; Mohammed Fattah; Younes Balboul; Said Mazer; Moulhime El Bekkali (Universitas Ahmad Dahlan, 2022)
In this paper, we present a study and design of a rectangular-shaped microstrip patch antenna with a rectangular shaped slot at the operating frequency is 28GHz, for fifth generation (5G) wireless applications, using the microstrip line technique for feeding. The objective of this slot is to contribute to the improvement of antenna performance. This antenna is built on a Roger RT duroid 5880 type substrate having a relative permittivity equal to 2.2, a height of h = 0.5 mm, and a loss tangent of 0.0009. The compact size of this antenna is 4.2 mm × 3.3 mm × 0.5 mm. The simulations of this antenna were performed using high-frequency structure simulator (HFSS) and computer simulation technology (CST) software whose main purpose is to confirm the results obtained for this proposed antenna. The results obtained during these simulations are as follows: resonant frequency of 27.97 GHz and reflection coefficient ) of -20.95 dB, bandwidth of 1.06 GHz, a gain of 7.5 dB, radiated power of 29.9 dBm, and efficiency of 99.83%. These results obtained by this proposed antenna are better than those obtained from already existing antennas that are published in current scientific journals. Consequently, this antenna is likely to satisfy the needs for 5G wireless communication applications.